Elizabeth - Kapur, Shekhar (Warner Bros : Warner Home Video, 2004)
England 1554, Under the rule of Queen Mary I, England has been reduced to a country sacked by financial and religious instability. When Mary dies the young Elizabeth (Cate Blanchett) is crowned Queen. While the country rejoices, Elizabeth relishes the return of her childhood sweetheart, Robert Dudley (Joseph Fiennes), but it advised to forget personal matters and addresses the problems facing the country from abroad. Sir William Cecil (Richard Attenborough), her chief adviser says she must marry to secure the realm. While she cares only for Dudley, Elizabeth realizes she has to exert her authority forcefully in court if she is to survive. With threats from both the French and the Spanish, and putting her only trust in her chief confident, Sir Francis Walshingham (Geoffrey Rush), she overcomes internal conspiracy and assassination attempts, wiping out all position to her leadership. No one is spared - except Dudley, who the Queen allows to survive as a reminder of the danger always confronting her. Her triumph signals both her personal strategy and astonishing courage to achieve national unity.